2019
DOI: 10.1039/c9nj00703b
|View full text |Cite
|
Sign up to set email alerts
|

A new efficient domino approach for the synthesis of coumarin-pyrazolines as antimicrobial agents targeting bacteriald-alanine-d-alanine ligase

Abstract: The inhibition of d-alanine-d-alanine ligase (Ddl) prevents bacterial growth, which makes this enzyme an attractive and viable target in the urgent search for novel effective antimicrobial drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
14
0
3
Order By: Relevance
“…Coumarins are well known antibacterial candidates [42][43][44][45][46][47][48], acting via different mechanisms. These include topoisomerase II DNA (gyrase) [49] or D-alanine-D-alanine ligase (DdlB) [50] inhibition, cell membrane integrity [51], or cytochrome biosynthesis disruption [52]. Coumarins, naturally occurring and/or synthetic, also show remarkable pharmacological properties as anticoagulants [53,54], anti-inflammatory [55], antioxidant [56], antiplatelet [57], anticarcinogenic [58][59][60][61][62][63] and antifungal agents [64].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins are well known antibacterial candidates [42][43][44][45][46][47][48], acting via different mechanisms. These include topoisomerase II DNA (gyrase) [49] or D-alanine-D-alanine ligase (DdlB) [50] inhibition, cell membrane integrity [51], or cytochrome biosynthesis disruption [52]. Coumarins, naturally occurring and/or synthetic, also show remarkable pharmacological properties as anticoagulants [53,54], anti-inflammatory [55], antioxidant [56], antiplatelet [57], anticarcinogenic [58][59][60][61][62][63] and antifungal agents [64].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoline scaffold possess well recognized antidepressant and anticonvulsant properties [148–150] . Additionally, it also has been served for antihypertensive, anti‐inflammatory, MAO enzyme inhibition [151] and antimicrobial potential [152] in recent years. Therefore, it could be taken as lead molecule to design some novel compounds with better inhibitory potential.…”
Section: Synthetic Approaches and Design Aspects Of Various Classes Omentioning
confidence: 99%
“…The inhibition of d ‐alanine– d ‐alanine ligase could prevent bacterial growth, so this enzyme is an attractive and viable target in the development of novel antibacterial agents. [ 58,59 ] The SAR study of coumarin–pyrazoline hybrids 19 (half‐maximal inhibitory concentration/IC 50 : 106 to >400 µM) indicated that hydroxyl, methyl, and methoxy groups at the para and meta position of phenyl ring (R 2 position) increased the inhibition activity against d ‐alanine– d ‐alanine ligase, whereas the introduction of phenyl ring into pyrazoline moiety (R 1 position) led to a loss of activity. [ 58 ] In particular, hybrids 19a,b (IC 50 : 106 and 111 µM) with the highest activity against d ‐alanine– d ‐alanine ligase also possessed promising activity (MIC: 14–40 µg/ml) against E. coli and S. aureus , and the activity was on the same level with that of d ‐cycloserine (MIC: 16 and 32 µg/ml).…”
Section: Coumarin–pyrazole Hybridsmentioning
confidence: 99%